2009
DOI: 10.1016/j.healthpol.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Drugs, sex, money and power: An HPV vaccine case study

Abstract: In this paper we compare the experiences of seven industrialized countries in considering approval and introduction of the world's first cervical cancer-preventing vaccine. Based on case studies, articles from public agencies, professional journals and newspapers we analyse the public debate about the vaccine, examine positions of stakeholder groups and their influence on the course and outcome of this policy process. The analysis shows that the countries considered here approved the vaccine and established re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 11 publications
0
32
0
1
Order By: Relevance
“…[3][4][5] As randomized controlled trials of the vaccine showed it to be highly efficacious in preventing vaccine-type-specific precancerous cervical lesions and AGW, 6,7 the vaccine received a great deal of attention from the scientific and medical communities, as well as from the general public. 8 Currently, the qHPV vaccine is available in .100 countries, many of which also have national qHPV immunization programs. 9 These programs are generally aimed at immunizing young girls before the onset of sexual activity when the possibility of previous HPV infection is low (eg, ages 9-13 years).…”
Section: What This Study Addsmentioning
confidence: 99%
“…[3][4][5] As randomized controlled trials of the vaccine showed it to be highly efficacious in preventing vaccine-type-specific precancerous cervical lesions and AGW, 6,7 the vaccine received a great deal of attention from the scientific and medical communities, as well as from the general public. 8 Currently, the qHPV vaccine is available in .100 countries, many of which also have national qHPV immunization programs. 9 These programs are generally aimed at immunizing young girls before the onset of sexual activity when the possibility of previous HPV infection is low (eg, ages 9-13 years).…”
Section: What This Study Addsmentioning
confidence: 99%
“…1 Medical professionals, public health experts, politicians, and parents disagreed about the merits of legislative mandates concerning the HPV vaccine. 2,3 Although many in the medical community supported the vaccine for its protective potential, other groups and parents criticized the mandates. Some opposed immunizing preteen girls against a sexually transmitted disease or believed that the vaccine would encourage sexual promiscuity.…”
Section: N June 2006 the Us Food And Drugmentioning
confidence: 99%
“…[2][3][4] As one of the first cancer-preventing vaccines, this vaccine received expedited approval in several countries and was the subject of intensive marketing, lobbying and public health campaigns around the world. 5 By 2012, it had been approved in almost 100 countries, many of which also implemented nationwide HPV vaccination programs aimed primarily at immunizing young girls before the onset of sexual activity. 6 Despite the popularity of large-scale immunization programs, HPV vaccination has faced a great deal of controversy regarding unanswered questions about the real-world effects of this vaccine.…”
mentioning
confidence: 99%